HUBUNGAN KEDISIPLINAN DAN PEMAHAMAN AYAT-AYAT AL-QUR’AN DENGAN AKHLAK SISWA - Vivi Novianti; Hunainah Hunainah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2020)
The objectives of this study were 1) to determine student discipline, 2) to determine the students 'understanding of the verses of the Koran, 3) to determine the students' morals, 4) to determine the relationship between discipline and student morals, 5) to determine the relationship between understanding the verses. -say of the Al-Qur'an students with student morals, 6) to determine the relationship between discipline and understanding of the verses of the Qur'an together with the students' morals. The method used in this research is a quantitative method with a descriptive approach, namely to obtain an overview of the relationship between discipline and understanding of the verses of the Qur'an related to morals (surah Al-Ahzab verse 21, surah Al-Ahqof verse 15 and surah Ali. Imron 110) with the morals of MAN 2 Serang City students. The result of the research states that discipline is included in the good category with a mean value of 127.72, understanding of the verses of the Qur'an is in the medium category with a mean acquisition of 73.92, student morals are in the very good category with mean acquisition of 151.44, the coefficient relationship The correlation between the discipline and the students' morals is 0.749, the correlation coefficient of understanding the verses of the Qur'an with the students' morals is 0.218 and the relationship between discipline and understanding of the verses of the Qur'an together with the students' morals has a correlation coefficient of 0.749 which means it has an influence on student morals by 74.9%.